Effect of ant attendance on aphid population growth and above ground biomass of the aphid's host plant - Afsane HOSSEINI; Mojtaba HOSSEINI; Noboru KATAYAMA; Mohsen MEHRPARVAR (European Journal of Entomology, 2017)
Ant-aphid mutualism is considered to be a beneficial association for the individuals concerned. The population and fitness of aphids affected by ant attendance and the outcome of this relationship affects the host plant of the aphid. The main hypothesis of the current study is that ant tending decreases aphid developmental time and/or increases reproduction per capita, which seriously reduces host plant fitness. The effect of attendance by the ant Tapinoma erraticum (Latreille, 1798) (Hymenoptera: Formicidae) on population growth and duration of different developmental stages of Aphis gossypii Glover (Hemiptera: Aphididae) were determined along with the consequences for the fitness of the host plant of the aphid, Vicia faba L., in greenhouse conditions. The initial aphid density was manipulated in order to study aphid performance due to density-dependent changes in ant attendance. The population growth rate of ant attended aphids was more than that of unattended aphids. However, the ratio of 1st-2nd nymphs to adults in aphid populations attended by ants was lower. The yields of bean plants on which the aphids were attended by ants were significantly greater than those of unattended plants. This study indicates that ants not only increase aphid fitness in terms of their population growth rate, but also benefit the host plant.